Effect of dietary protein on fat-free mass in energy restricted, resistance-trained individuals: An updated systematic review with meta-regression - Refalo, M. C.; Trexler, E. T.; Helms, E. R. (Strength and Conditioning Journal, 2025)
Individuals often restrict energy intake to lose fat mass (and body mass [BM]) while performing resistance training (RT) to retain fat-free mass (FFM). Therefore, the aim of the present systematic review with meta-regression was to explore (a) the pattern and strength of the dose-response relationship between daily dietary protein intake and FFM change, and (b) whether intervention duration, energy deficit magnitude, baseline body fat percentage (BF%), and participant sex influence this relationship. Studies were included if they involved a standardized RT protocol with nonobese, energy-restricted (experiencing fat mass loss) individuals with a minimum of 3 months RT experience. Of 916 retrieved studies, data were extracted from a total of 29 studies. Bayesian methods were used to fit linear and nonlinear meta-regression models and estimate effect sizes, highest density credible intervals, and probabilities. Results suggest a >97% probability of a linear dose-response relationship between daily protein intake [g/kgBM: ß = 0.07 (95% highest density interval [HDI]: -0.01 to 0.14), and g/kg/FFM: ß = 0.06 (95% HDI: 0.01 to 0.12)] and favorable FFM changes. The relationship is stronger when protein intake is expressed relative to FFM, in interventions longer than 4 weeks, in men, and when BF% is lower. Overall, the heterogeneity between studies renders our findings exploratory.